Ab initio study for structure, electric properties and light emission of linear-trans-quinacridone - Susanto, Agus (Animo Repository, 2006)
The structure, electric properties and emission rate of linear-trans-quinacridone are investigated within the density functional theory (DFT) calculations. We find the structure of the molecule to be planar with an energy gap of 3.06 eV. The emission lifetime from the lowest unoccupied molecular orbital (LUMO) to the highest occupied molecular orbital (HOMO) of this material is found to be 24 ns, which is in good agreement with experimental results.